2013
DOI: 10.1371/journal.pone.0077722
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin1 Channel Proteins in the Zebrafish Retina Have Shared and Unique Properties

Abstract: In mammals, a single pannexin1 gene (Panx1) is widely expressed in the CNS including the inner and outer retinae, forming large-pore voltage-gated membrane channels, which are involved in calcium and ATP signaling. Previously, we discovered that zebrafish lack Panx1 expression in the inner retina, with drPanx1a exclusively expressed in horizontal cells of the outer retina. Here, we characterize a second drPanx1 protein, drPanx1b, generated by whole-genome duplications during teleost evolution. Homology searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 53 publications
10
74
0
Order By: Relevance
“…A plethora of membrane channels are reportedly regulated by pH changes and emerging evidence has suggested that Panx1 might be part of this group (Kurtenbach et al . ). Uninjected and Panx1‐expressing oocytes were exposed to a 1 unit pH increase (to pH 8.4) or decrease (to pH 6.4) to determine whether a pH change alters Panx1‐mediated ion conductance and ethidium uptake (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A plethora of membrane channels are reportedly regulated by pH changes and emerging evidence has suggested that Panx1 might be part of this group (Kurtenbach et al . ). Uninjected and Panx1‐expressing oocytes were exposed to a 1 unit pH increase (to pH 8.4) or decrease (to pH 6.4) to determine whether a pH change alters Panx1‐mediated ion conductance and ethidium uptake (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…We detected a slight reduction in Panx1‐mediated conductance at alkaline pH and a larger pH‐dependent effect on ethidium uptake (increase with alkalization and decrease with acidification), the latter in accordance with a previous report (Kurtenbach et al . ). These results underscore the permeant‐selective states of Panx1 and specifically illustrate an activation regime that predominantly targets the ethidium flux.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ATP blocked the slow component of feedback, indicating the slow component depends on ATP. Note this concentration of ATP does not block Panx1 channels [20]. (C) Normalized mean feedback responses in seven cones in control (black) and in 50 µM ARL67156, a blocker of NTPDase (red).…”
Section: Resultsmentioning
confidence: 99%
“…This assay is a variation of the ethidium bromide uptake assay previously reported (Prochnow et al, 2009; Kurtenbach et al, 2013). Transfected Neuro2a cells grown for 48 h in 3.5 cm MatTek cell culture dishes were incubated with 10 μM of ethidium bromide in complete growth medium for 10 min at 37°C and 5% CO 2.…”
Section: Methodsmentioning
confidence: 99%